EFFECTIVENESS OF THE PBL MODEL WITH THE TPS REVIEWED FROM CRITICAL THINKING ABILITY OF GRADE 5 STUDENTS IN MATHEMATICS TEACHING - Elza Pristy Latifah; Wahyudi Wahyudi; Yohana Setiawan (Universitas Negeri Makassar, 2019)
The purpose of this study was to examine the differences in effectiveness of PBL learning models with TPS in terms of the critical thinking skills of elementary school students in mathematics. This research is a quasi-experimental study. In this study, the Non-equivalent Control Group Design design is used to investigate the effects of the two variables used. In this study 19 students at Bacem Elementary School and 19 students at Waru Elementary School, Jepon District, Blora Regency. The two groups were given different treatments, namely the PBL learning model was treated in the experimental group at Bacem SDN, and the TPS model was treated in the control group at Waru Elementary School. Based on the results of the study, H_oditotak and H_a were accepted. The analysis in this study used the Ngain test to determine the increase in the average value of the results of the pretest and posttest. This is based on the results of the NGain analysis showing an increase in value after being given PBL treatment of 0.64, while the increase in value after being given TPS treatment was 0.53. Based on all analysis results, it can be concluded that there are significant differences in effectiveness in this study. Evidently the application of PBL learning models has a higher level of effectiveness when compared to the TPS learning model of the critical thinking skills of fifth grade students in mathematics